Variants of Conjoined Twins - Two Case Reports - Akhtar, Nahreen; Karim, Sabina; Parveen, Tabassum; Sayeeda, Syeda; Begum, Firoza (Bangabandhu Sheikh Mujib Medical University Journal, 2012)
Conjoined twins are identical twins whose bodies are joined in utero. Parasitic twins occur when a twin embryo begins developing in utero, but the pair does not fully separate, and one embryo maintains dominant development at the expense of the other which becomes vestigial. Vestigial twin appears as parasitic because it is incompletely formed or wholly dependent on the body function of the complete fetus. The independent twin is called the autosite. In conjoined twins both remain healthy. In this study we have presented one parasitic twin and another conjoined twin. In 1st case a 28 yrs old lady delivered a female parasitic twin by caesarean section due to failure of induction of labour. Unfortunately the baby died on 3rd postoperative day. In 2nd case, a 25years old lady diagnosed as a case of conjoined twin by ultrasonography for the first time at her 35wks of pregnancy. Emergency caesarean section was arranged on the day of admission as she started labour pain. A conjoined twin was delivered which were joined at thorax and abdomen and both were alive. Parents were offered surgical separation but they refused it and take the babies home. DOI: http://dx.doi.org/10.3329/bsmmuj.v5i1.11027 BSMMU J 2012; 5(1):65-68